Weekend Effect in the Banking and Financial Services Sector : An Empirical Evidence from India - Mittal, Arjun; Das, Hritwiza; Mittal, Anand; Thukral, Sonal (Indian Journal of Finance, 2025)
Purpose : The weekend effect exhibited a systematic pattern in the market returns based on the days of the week, which appeared to deviate from the efficient market theory. However, several studies also showed that the anomaly either did not exist or had disappeared with time, resulting in contradictory evidence in the existing literature. Thus, this study aimed to investigate the presence of the weekend effect in the Indian banking and financial service sectors. Methodology : The NIFTY Bank Index and NIFTY Financial Services Index were taken as representatives of these two sectors. Five years (2019–2023) of market returns were analyzed using OLS and GARCH models to study the presence of weekend effects in these sectors. Findings : No significant evidence of the weekend effect was found in either sector. However, the presence of the ARCH effect indicated volatility clustering, suggesting inefficiency. Practical Implication : The findings have implications for investors, arbitrageurs, hedgers, portfolio managers, as well as regulators and academicians. Investors will not earn any extra profit by creating positions based on the day of the week. Originality : The study contributed to the existing literature on calendar anomalies and market efficiencies in the Indian market, as well as specific economic sectors, adopting a volatility-adjusted modelling technique. In the past few years, this sector has gone through major structural and technological changes, including pandemic-related volatility, inducing changes in market sentiments and efficiency. Thus, this study offered a more contemporary as well as sector-specific perspective on market efficiency.